The role of iodine in stunting - Fifin Dian Safitri; Siti Haryati (Arsip Keilmuan Gizi (AKG), 2024)
Stunting is a significant nutritional problem in Indonesia, caused by various factors, including iodine deficiency. Iodine is crucial in child growth and development, especially in brain and nervous system development. This study aims to analyze the relationship between iodine intake and the incidence of stunting in children. The method used is a literature review using indexed sources such as Google Scholar, PubMed, and Google Books, with the keywords "child," "stunting," and "iodine." The results showed a significant relationship between iodine intake and stunting incidence. Iodine deficiency in pregnant women can increase the risk of stunting in children, and iodized salt consumption can reduce the risk of stunting. In addition, other factors, such as parenting patterns, low birth weight, and immunization status can also affect the incidence of stunting. In conclusion, adequate iodine intake is crucial in preventing stunting in children, and efforts to increase iodine intake must be made to overcome the problem of stunting in Indonesia.